Happiness: The Potential Power of Environment - Clifford Sosis (Baltic International Yearbook of Cognition, Logic and Communication, 2012)
Many scientists have argued that they can determine to what extent human happiness levels are controlled by genes by comparing the average happiness levels of identical twins raised apart. If we discover that identical twins raised apart tend to be more hedonically similar than fraternal twins raised apart, this is interpreted as evidence for the thesis that genes have a strong influence on our happiness levels. If identical twins are hedonically dissimilar, as dissimilar as fraternal twins raised apart, this has been taken as evidence for the thesis that happiness levels are determined in large part by the environment. I shall show that that these interpretations of these studies rely on a set of false assumptions. There is no good evidence our genes determine how happy we can be.